Are religions for sale? Evidence from the Swedish church revolt over same-sex marriage - Niklas Bengtsson (Uppsala University, Department of Economics, 2017)
Religious leaders sometimes condemn progressive social norms. In this paper, I revisit David Hume's hypothesis that secular states can "bribe" churches into adopting less strict religious doctrines. The hypothesis is difficult to test due to reverse causality: more liberal theologies may attract more political support in the first place. To circumvent this problem, I focus on a theological conflict over same-sex marriage within the Church of Sweden and take advantage of political regulations that effectively make some parishes shareholders of the church's state-protected property. The shares used for statistical identification are tied to property rights assigned more than 300 years ago, and they cannot be sold, traded or amended by the individual parishes. I find that priests in shareholding parishes are less likely to publicly oppose same-sex marriage. The effect is stronger in parishes with more conservative members. The combined results are consistent with a model of clerical opportunism, in which access to political rents increases the clergy's loyalty to the political sponsors relative to the local community.
urn:nbn:se:uu:diva-317443
Keywords: H2; H3; Z12; 330; religious orthodoxy; same-sex marriage; subsidies; rent-seeking; religious market hypothesis